Personal Data Protection as an Expression of Personalism - Chojara-Sobiecka, Małgorzata; Kroczek, Piotr (Philosophy and Canon Law, 2021)
Human-related issues are the objected personalism. One of the current problems contemporarily recognized and widely known is data protection. The article aims to present a mutual connection between legal regulations of data protection, taking under consideration GDPR, and personalism. The conclusion is that there are many elements in legal regulations that justify the conviction that the protection of personal data can be seen as an expression of personalism.